A Comparative Study of Effectiveness of Induction Chemotherapy between Two Regimens in Locally Advanced Head and Neck Cancer (The Planet, 2024)
Introduction: Locally advanced head and neck cancer occurs when the tumor has grown beyond its point of origin but hasn't spread to other parts of the body. This cancer usually impacts the oral cavity, throat, larynx, and other structures in the head and neck area. Treating and predicting outcomes for locally advanced head and neck cancer can be quite challenging. Objective: The objective of this study is to evaluate the efficacy of the Leucovorin, 5-FU, Cisplatin (LFP) regimen in comparison to the Docetaxel, Cisplatin, 5-FU (DCF) regimen followed by external beam radiotherapy for managing advanced head and neck cancer and achieving locoregional control.  Methods and Materials: The study was conducted in the Department of Oncology at Khwaja Yunus Ali Medical College and Hospital in Enayetpur, Sirajgonj. The study took place from October 2017 to March 2019. Patients who met the study's criteria and visited the KYAMCH Oncology OPD from October 2017 to March 2019 received induction chemotherapy using the LFP and DCF regimen, followed by EBRT. Results: More men responded to treatment, especially with complete response (64.5%). Older patients (50-59) had higher complete response rates than younger (60-69). Moderate differentiation had the highest complete response rate (25%) compared to well and poorly-differentiated hospitalizations for toxicity management. Overall, most were mild (Grade 2). Neutropenia was most common (26.7% Grade 2, 13.3% Grade 3). Arm A had more radiotherapy-related toxicity than Arm B. Conclusion: Managing locally advanced head and neck cancer requires a comprehensive and team-based approach. Significant progress has been made in treatment options and supportive care, leading to better outcomes. However, getting the best results still depends on detecting issues early. Regular screening and awareness of risk factors are essential for early intervention and effective risk management.
Keywords: Neutropenia; Thrombocytopenia; Differentiation; Mucositis; Alopecia; Chemotherapy